73.4k views
0 votes
Complete the square please.

Complete the square please.-example-1
User Dimgold
by
5.4k points

1 Answer

6 votes

Answer:

(x-3)^2 + (y+2)^2 = 9^2

Explanation:

x^2 -6x+y^2+4y-68 = 0

Complete the square

x^2 -6x+y^2+4y-68+68 = 0+68

x^2 -6x+y^2+4y = 68

Find the term to add for x

-6 /2 = -3 -3^2 = 9

Find the term to add for y

4/2 =2 2^2 = 4

Add 9 and 4

x^2 -6x+9+y^2+4y+4 = 68+9+4

(x-3)^2 + (y+2)^2 = 81

(x-3)^2 + (y+2)^2 = 9^2

The standard form is

(x-h)^2 + (y-k)^2 = r^2 where (h,k) is the center and r is the radius

User Tommo
by
5.3k points